Artificial intelligence in social services: state of the art and possible future developments - Minguijon, Jaime; Serrano-Martinez, Cecilia (Cuadernos de Trabajo Social, 2022)
The aim of this essentially theoretical paper is to analyze the degree to which Spanish social services have adapted to digital technologies, focusing specifically on the presence of artificial intelligence (AI). The fundamental contribution of the paper is the proposal of a model to test the presence of AI in social services, at the same time as designing a strategy for its integration into the different social services systems. This proposal is built through two vectors: identifying the fundamental activities or stages of social intervention in addition to access, planning and evaluation of the system; and proposing three phases or levels of AI integration according to the extent of the role played by professionals. A review of the scientific literature together with a search for AI implementation initiatives in social services identified successful experiences in Spain that can be included in some areas of the model. The notable current advances in this field are often unknown beyond their specific contexts or field of expertise. But there is a long way to go, and the remaining steps can only be taken with decisive public support.